Commodification of Religion and Pop Culture on Social Media: Netnographic Studies - Naili Ni'matul Illiyyun (Jurnal Penelitian, 2018)
Instagram accounts owned by cultural industry have been followed by millions of followers and are not limited to a group of people in a country because cyberspace creates unlimited communities. Cultural industries that use Instagram place halal (allowed in Islam) and syar'i (based on Islamic law) labels as important elements in promoting their commodities. The following article tries to look at the commodification of several posts on Instagram that are related to religious identity and the implications that are formed by the cultural industry in Muslim communities. The following qualitative research is analyzed by content analysis based on data collection - neographic studies - from several Instagram accounts, such as travel, fashion, and cosmetics agent acoounts which utilize Islamic attributes. The results of this study indicate that the cultural industry always introduces new trends of pop culture through Instagram by using religious attributes, such as using the terms halal, syar'i, or Muslim. Religion as an agency is widely used by the cultural industry in advertising its commodities. In addition, the agency is a tool to persuade consumers to buy commodities and at the same time it is able to identify consumers as pious and modern Muslims.